Aus dem Buch des Lebens: Zum Status der Philologie bei Benjamin und Gramsci / From the Book of Life: Walter Benjamin’s and Antonio Gramsci’s Philological Methods - Loheit, Jan (International Gramsci Journal, 2023)
For Antonio Gramsci and Walter Benjamin, whose texts from the time of the fascist terror in Europe are still widely discussed, philology was an indispensable instrument of their criticism. Philological criticism, which gained a political and epistemological dimension in their works, plays a crucial role in their analyses of fascism, questions of historiography and their examinations of Marxism. The writings that emerged during this period, Gramsci’s Prison Notebooks and Benjamin’s Arcades Project, are known to have remained fragments. In this article, the focus is on the philological impulse on which these writings were based and which, as will be shown, corresponded to a specific structure of thought in which matter and method tend to fuse.